Pengaruh Word Of Mouth dan Switching Cost Terhadap Keputusan Pembelian dan Loyalitas - Iha Haryani Hatta; Setiarini Setiarini (JURNAL ILMIAH MANAJEMEN & BISNIS, 2018)
The reciprocal of WOM (word of mouth) & switching cost into  purchasing and loyality. The purpose of research  The affect WOM  and switching cost of the decision to purchase & loyalty; The affect  the decision to purchase of loyalty . The population this research are  200 Meat Me Café & Butchery’s customers in jakarta  who were randomly selected by mixed data with SEM, AMOS21 program . The results of research explained that WOM and switching cost are influential  decision to buy & loyalty, and the decision to buy influences loyalty. The WOM & switching cost substantiate same as purchase of the decision, and loyalty.